2002
DOI: 10.1093/nar/30.7.1500
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of a parallel-stranded DNA duplex at atomic resolution

Abstract: DNA dodecamers have been designed with two cytosines on each end and intervening A and T stretches, such that the oligomers have fully complementary A:T base pairs when aligned in the parallel orientation. Spectroscopic (UV, CD and IR), NMR and molecular dynamics studies have shown that oligomers having the sequences d(CCATAATTTACC) and d(CCTATTAAATCC) form a parallel-stranded duplex when dissolved at 1:1 stoichiometry in aqueous solution. This is due to the C:C+ clamps on either end and extensive mismatches i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
4
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 39 publications
6
73
4
1
Order By: Relevance
“…The probabilities of loops or bubbles, helical segments, and unzipping ends in melting DNA, folded and unfolded states (found to be unique for each sequence), that were compatible with CD spectra difference for structural characterization of nucleic acids (Mergny et al, 2005), the alternative conformations that coexist in equilibrium and the range of their fluctuations (Mergny et al, 2005) were described for antiparallel-stranded oligoduplexes. The parallel stranded oligoduplexes were studied before with CD spectroscopy and NMR for structural conformation study (Gundry et al, 2003;Ramsing and Jouim, 1988;Parvathy et al, 2002;Robinson and Wang, 1993;Dolinnya et al, 1997;Aboul-ela et al, 1994;Rippe et al, 1989;Allwi and Santa Licia, 1998;Tchurikov et al, 1989;Bhoumik et al, 1995;Otto et al, 1991;Klysik et al, 1991;Rippe et al, 1992;Williamson, 1994;Wang and Patel, 1994). In this study, the thermal denaturation profiles of parallel stranded oligoduplexes during UV-spectroscopy and fluorescence spectroscopy, for the first time, were shown to follow the similar patterns as were described for antiparallel stranded oligoduplexes.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The probabilities of loops or bubbles, helical segments, and unzipping ends in melting DNA, folded and unfolded states (found to be unique for each sequence), that were compatible with CD spectra difference for structural characterization of nucleic acids (Mergny et al, 2005), the alternative conformations that coexist in equilibrium and the range of their fluctuations (Mergny et al, 2005) were described for antiparallel-stranded oligoduplexes. The parallel stranded oligoduplexes were studied before with CD spectroscopy and NMR for structural conformation study (Gundry et al, 2003;Ramsing and Jouim, 1988;Parvathy et al, 2002;Robinson and Wang, 1993;Dolinnya et al, 1997;Aboul-ela et al, 1994;Rippe et al, 1989;Allwi and Santa Licia, 1998;Tchurikov et al, 1989;Bhoumik et al, 1995;Otto et al, 1991;Klysik et al, 1991;Rippe et al, 1992;Williamson, 1994;Wang and Patel, 1994). In this study, the thermal denaturation profiles of parallel stranded oligoduplexes during UV-spectroscopy and fluorescence spectroscopy, for the first time, were shown to follow the similar patterns as were described for antiparallel stranded oligoduplexes.…”
Section: Introductionsupporting
confidence: 57%
“…These structures of presumptive parallel oligoduplexes were not determined with NMR. NMR data as well as CD data of various parallel oligoduplexes (Gundry et al, 2003;Ramsing and Jouim, 1988;Parvathy et al, 2002;Robinson and Wang, 1993;Dolinnya et al, 1997;Aboul-ela et al, 1994;Rippe et al, 1989;Allwi and Santa Lucia, 1998;Tchurikov et al, 1989;Bhoumik et al, 1995;Otto et al, 1991;Klysik et al, 1991;Rippe et al, 1992;Williamson, 1994;Wang and Patel, 1994). had shown that, despite from the usual Watson-Crick base pairing, these right-handed helical parallel stranded conformation generally included reverse Watson-Crick base pairing, Hoogstein G:C + base pair, Donhue G:C …”
Section: Spectra Analysis Of Oligomersmentioning
confidence: 99%
“…In support of this possibility, previous studies have demonstrated and characterized A·G, A·C, and A·A mismatched base pairs (72)(73)(74)(75)(76)(77)(78). Further, the P1 primer may also randomly hybridize to RNAs (including mRNAs, rRNAs, and tRNAs) at 42°C during cDNA synthesis via matched (A·T and G·C) and previously demonstrated mismatched (G·T, G·A, A·C, T·C, G·G, A·A, T·T, and C·C) base pairs (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84). Moreover, random primers target RNAs and, hence, have been used to analyze a broad spectrum of RNAs.…”
Section: Resultsmentioning
confidence: 71%
“…While the energy of the latter can be calculated using conventional methods, these do not allow the calculation of the energy of a parallel duplex. Parallel-stranded DNA duplex structures are known from X-ray studies (Rippe & Jovin 1992;Parvathy et al 2002) and although no-one has synthesized an RNA equivalent, there is little to make one suspect that it could not exist. By analogy with the DNA structures, it can be expected that this would be much less stable than the reverse complementary duplex.…”
Section: Conceptual Modelsmentioning
confidence: 99%